1, n‐Hydrogen‐Atom Transfer (HAT) Reactions in Which n≠5: An Updated Inventory. Issue 49 (24th October 2014) - Nechab, Malek; Mondal, Shovan; Bertrand, Michèle P.
Abstract Hydrogen‐atom transfer (HAT) counts amongst the most widely investigated routes to carbon‐centered radicals. Intramolecular processes involving 1, 5‐HAT are widespread to promote regioselective radical "CH activation". The aim of this review is to draw up a comprehensive inventory of the less commonly encountered 1, n‐radical translocations (n≠5) with the aim to update this topic with the most recent relevant data.